2019
DOI: 10.1016/j.tcb.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: Catching the Light in Zebrafish

Abstract: Extracellular Vesicles circulate in body fluids of all organisms and participate in intercellular cross-organ communication. Tracking and understanding these nanosized objects have been hampered by limited resolutive imaging and adapted animal models. The use of zebrafish embryos now allows to probe them at unprecedented spatio-temporal resolution, using light and electron microscopy. This enables the study of endogenous physiological EVs and pathological EVs side by side, and further unravel their biogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Our findings complement recent studies that describe the labelling, biodistribution and potential functional roles of exogenous tumour derived and endogenous CD63+ EVs in larval zebrafish (Hyenne et al, 2019;Verweij et al, 2019b). The described techniques and advancements in the use of zebrafish for in vivo EV research pave the way for investigations into multiple homeostatic and pathophysiological states (Verweij et al, 2019a) and the involvement of endogenous vesicles in cellular processes such as tissue regeneration.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings complement recent studies that describe the labelling, biodistribution and potential functional roles of exogenous tumour derived and endogenous CD63+ EVs in larval zebrafish (Hyenne et al, 2019;Verweij et al, 2019b). The described techniques and advancements in the use of zebrafish for in vivo EV research pave the way for investigations into multiple homeostatic and pathophysiological states (Verweij et al, 2019a) and the involvement of endogenous vesicles in cellular processes such as tissue regeneration.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, it was reported that a zebrafish transgenic line that expresses human CD63 fused with pHluorin under the control of tissue-specific promoter/enhancer can be used to visualize the release and uptake of EVs in vivo. A role for EVs in the formation of metastatic niches in vivo could also be determined by tracking EVs shed from melanoma cells in zebrafish embryos, demonstrating that zebrafish is an excellent model for the study of EVs 50 . In the present study, our transplantation assays clearly demonstrated that mCherry + particles observed in trap:GFP + cells are derived from EVs shed from OBs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all publications exclusively reported the use of mice for exosome biodistribution analysis. Recently, increasing evidence suggests that the use of zebrafish is a promising new approach to study in vivo physiology and pathology of exosomes [101]. Indeed, the transparency and small size of the zebrafish embryo enables live whole-body imaging analysis for better understanding of biodistribution including exosome uptake and fate.…”
Section: Determination Of Exosome Dosementioning
confidence: 99%